“New” Realism as a Problem of Method - Marko Bosnić (Meta: Research in Hermeneutics, Phenomenology and Practical Philosophy, 2014)
The development of the discussion on “Speculative Realism” and “Speculative Materialism” is very well documented. However, in order to better understand the overall project of this “New Realism” it is helpful to draw light to the genealogy and context in which the problem evolved in. In this paper, I map out a genealogy of the complex problem of “New Realism” in order to understand what it is that is “new” about this realism. The central argument of the paper is that the new problem of realism is in essence a question of method, resulting from a tension between philosophical and sociological epistemology.